CFD Techniques and Thermo-Mechanics Applications (Springer International Publishing, 2018)
This book focuses on CFD (Computational Fluid Dynamics) techniques and the recent developments and research works in thermo-mechanics applications. It is devoted to the publication of basic and applied studies broadly related to this area. The chapters present the development of numerical methods, computational techniques, and case studies in the thermo-mechanics applications. They offer the fundamental knowledge for using CFD in real thermo-mechanics applications and complex flow problems through new technical approaches. Also, they discuss the steps in the CFD process and provide benefits and issues when using the CFD analysis in understanding of complicated flow phenomena and its use in the design process. The best practices for reducing errors and uncertainties in CFD analysis are also discussed. The presented case studies and development approaches aim to provide the readers, such as engineers and PhD students, the fundamentals of CFD prior to embarking on any real simulation project. Additionally, engineers supporting or being supported by CFD analysts can benefit from this book.